Hereditary Cerebral Hemorrhage with Amyloidosis -Dutch Type: A Study of Fibrinolysis - Haan, J; Kluft, C; Leebeek, F W G; de Bart, A C W; Buruma, O J S; Roos, R A C (Thrombosis and Haemostasis, 1992)
In view of reported associations between increased bleeding tendency and systemically decreased α2-antiplasmin in patients with systemic amyloid deposition we studied α2-antiplasmin, fibrinogen, C-reactive protein and blood levels of locally produced endothelial hemostasis factors in the acute and quiescent phase in 16 patients with hereditary cerebral hemorrhage with amyloidosis - Dutch type (HCHWA-D).None of the factors measured in the quiescent phase of the disease was abnormal. In the acute phase, shortly after a stroke, only factor VIII: Ag was evidently elevated. We concluded that systemic abnormalities in the part of the fibrinolysis system studied are not likely to be responsible for multifocal and recurrent cerebral hemorrhages in HCHWA-D. The role of an elevated factor VIII: Ag level in the acute phase is unclear.